1993
DOI: 10.1159/000227213
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Ablation of Liver Tissue by High-Intensity Focused Ultrasound

Abstract: High-intensity focused ultrasound (HIFU) may produce a well-delineated lesion of coagulation necrosis in deep organs, by means of an extracorporeal transducer. Applications of this method to the liver in animal models have been studied for many years. The effects of HIFU on the normal liver parenchyma and on hepatic tumors are reviewed. In the normal rabbit liver in vivo we showed the relation between intensity levels and exposure times and the need to adapt intensity to the depth of the target. No severe comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 16 publications
1
36
0
1
Order By: Relevance
“…Similar lesions have been observed when high-intensity focused ultrasound was used to create lesions in noncardiac tissue. 1,5,7,11,15 The pathology of the acute lesions noted in the present study is similar to that of the well-demarcated lesions created with radiofrequency energy. 16 -18 This type of well-demarcated lesion is not believed to be associated with a risk of proarrhythmia.…”
Section: Pathology and Mechanism Of Lesion Formationsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar lesions have been observed when high-intensity focused ultrasound was used to create lesions in noncardiac tissue. 1,5,7,11,15 The pathology of the acute lesions noted in the present study is similar to that of the well-demarcated lesions created with radiofrequency energy. 16 -18 This type of well-demarcated lesion is not believed to be associated with a risk of proarrhythmia.…”
Section: Pathology and Mechanism Of Lesion Formationsupporting
confidence: 74%
“…6 Therapeutic ultrasound has been used to treat a variety of conditions. 1,2,4,5,[7][8][9][10][11][12][13][14] However, the use of extracardiac ultrasound to ablate functioning myocardium has not been reported. The purpose of this study was to determine whether extracorporeal focused ultrasound can be used to create atrioventricular (AV) block within the beating canine heart.…”
mentioning
confidence: 99%
“…Research results of home and abroad using animals showed that HIFU can safely and effectively destroy inner liver tissue or liver transplant tumor [23][24][25][26][27][28][29][30] . Clinic results showed that HIFU can also treat liver cancer securely and effectively [11,31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of ultrasound thermal therapy [1][2][3][4][5] is to use high intensity, short-duration, focused ultrasound [6][7][8] to deliver enough energy into a specific tumor volume such that tissue necrosis is formed and the overheating of the intervening normal tissue can be avoided [2,9]. The external ultrasound heating is a noninvasive and very flexible modality for heating deep-seated tumors for its vast penetration and focusing ability.…”
Section: Introductionmentioning
confidence: 99%